Integrating a risk-oriented approach into bank investment management under market volatility - V. V. Shlonchak (Економіка, управління та адміністрування)
In the current context of heightened financial market volatility and growing instability of the investment environment, the issue of enhancing the efficiency of bank investment management has become increasingly critical. A limited consideration of risk in decision-making undermines the objectivity of asset return assessments and complicates the development of an optimal portfolio structure.